How they find us: a mixed methods study of international student journeys to higher education in the Midwest - Lee, Michael W. (University of Wisconsin--Stout, 2018)
The purpose of this mixed methods study was to investigate international student's pursuit of an associate or undergraduate degree at selected public higher education institutions (HEI's) in the upper Midwest. Through surveys distributed to 423 international students and interviews with 12 of them, the research sought to identify key expectations and experiences which influence a student's choice to attend one of the institutions featured in the study. With nearly a 55% response rate, the results showed that a majority of the international students first heard of the institution through a friend or family member. Aligned with findings from other studies, a majority of these students were self-funded or funded with the help of relatives. Two-thirds of the students reported having recommended the institution to their friends and family, highlighting the satisfaction with these institutions once they arrive. International students in the study tended to persist through tremendous challenges both before and during their educational experience, but these adversities are what kept them motivated. Findings from this study can be used to improve the student-institution match, helping teaching-focused HEI's in the Midwest provide the information and services needed to attract, recruit and retain the students that are most likely to enroll and persist at their college or university.
Keywords: Education, Higher; College choice; Motivation in education